2016
DOI: 10.17743/jaes.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Band Allocation (PBA) for the Rendering of Vertical Image Spread with a Vertical 2D Loudspeaker Array

Hyunkook Lee

Abstract: Two subjective experiments were conducted to examine a new vertical image rendering method named "Perceptual Band Allocation (PBA)," using octave bands of pink noise presented from main and height loudspeaker pairs. The PBA attempts to control the perceived degree of vertical image spread (VIS) by a flexible mapping between frequency band and loudspeaker layer based on the desired positioning of the band in the vertical plane. The first experiment measured the perceived vertical location of the phantom image o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…The results presented here suggest that the vertical localization cues from an elevated 8 kHz octave-band source have dominance over a lower positioned correlated source, when both are presented simultaneously. A large spectral notch around 8 kHz (caused by the pinna from the main-layer loudspeaker direction) is likely to be the cause of this effect, resulting in more energy for the 8 kHz band from the height-channel direction [35]. Furthermore, the downward extension following decorrelation suggests that both loudspeaker signals might be perceived independently at the same time, with the decorrelation process reducing the height dominance to "un-mask" the main-layer loudspeaker.…”
Section: Discussion Of Absolute Testing Resultsmentioning
confidence: 99%
“…The results presented here suggest that the vertical localization cues from an elevated 8 kHz octave-band source have dominance over a lower positioned correlated source, when both are presented simultaneously. A large spectral notch around 8 kHz (caused by the pinna from the main-layer loudspeaker direction) is likely to be the cause of this effect, resulting in more energy for the 8 kHz band from the height-channel direction [35]. Furthermore, the downward extension following decorrelation suggests that both loudspeaker signals might be perceived independently at the same time, with the decorrelation process reducing the height dominance to "un-mask" the main-layer loudspeaker.…”
Section: Discussion Of Absolute Testing Resultsmentioning
confidence: 99%
“…The present author [23] showed the elevation effect for the phantom images of octave-band pink noises as well as for broadband pink noise for the 60…”
Section: Introductionmentioning
confidence: 58%
“…Voice of God) channels to provide an immersive listening experience. While the VBAP [35] is widely considered as a standard technique for 3D sound panning, new techniques for 3D sound recording [39][40][41] and upmixing [42][43][44] are being developed. Furthermore, the recently standardized MPEG-H 3D audio codec [45] offers a highly efficient, object-based coding and transmission of 3D audio for domestic broadcasting.…”
Section: Practical Implications For 3d Sound Recording and Renderingmentioning
confidence: 99%
“…Another reason for a lack of significant VIS difference between the 'High' frequency band conditions in the subjective testing could be related to the "pitch-height effect" [24,26,27] and "directional bands effect" [28,29]. From the directional band research, it is known that 4 kHz and 16 kHz bands tend to be perceived in front and an 8 kHz band is often perceived above (if presented under anechoic conditions).…”
Section: High Frequency Band Discussionmentioning
confidence: 99%
“…From the directional band research, it is known that 4 kHz and 16 kHz bands tend to be perceived in front and an 8 kHz band is often perceived above (if presented under anechoic conditions). Similarly, when octave-band noise signals are presented at ear height from in front of the listener, a "pitch-height effect" occurs which sees the 8 kHz octave-band elevated upwards (towards the position of the height-channel loudspeaker); whereas the 16 kHz band is localised towards the main-channel loudspeaker and 4 kHz is perceived somewhere between the two [24,26]. Wallis and Lee [27] have demonstrated that this effect also occurs when coherent octave-bands are presented in vertical stereophony, i.e., the same signal reproduced in a main-layer loudspeaker and a height-layer loudspeaker simultaneously (both of which are located in the median plane, similar to the test condition in the current experiment).…”
Section: High Frequency Band Discussionmentioning
confidence: 99%